2017
DOI: 10.3382/ps/pew343
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Campylobacter jejuni multilocus sequence types isolated from chickens in Poland

Abstract: Poultry is recognized as the most important source of food-related transmission of Campylobacter jejuni to humans and campylobacteriosis is the most commonly reported zoonotic bacterial disease in the European Union. It has been documented that C. jejuni is genetically diverse and analyses of bacterial isolates usually show a large strain variety. Therefore, molecular typing of strains represents an important tool to study the genetic diversity of isolates and to trace individual strains that cause human infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
3
28
0
Order By: Relevance
“…Our previous study demonstrated that C. jejuni strains with ST6411 and ST257 were predominant among chickens in Poland, representing a total of 31.5% isolates tested [15]. These sequence types were also often identified in chicken sources in the present investigation although they were not as common as before (a total of 58 out of 451 isolates; 12.7%).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Our previous study demonstrated that C. jejuni strains with ST6411 and ST257 were predominant among chickens in Poland, representing a total of 31.5% isolates tested [15]. These sequence types were also often identified in chicken sources in the present investigation although they were not as common as before (a total of 58 out of 451 isolates; 12.7%).…”
Section: Discussionsupporting
confidence: 56%
“…MLST was carried out as described by Colles and Maiden [7] and Dingle et al [8]. Amplifications of the seven housekeeping genes that are included in the analysis scheme (aspA, glnA, gluA, glyA, pgm, tkt, uncA) were separately performed in a final volume of 25 μl PCR reaction as described previously [15]. The primers used for the amplification and sequencing of the genes and the PCR protocols were available at the Campylobacter MLST website (http:// pubmlst.org/campylobacter).…”
Section: Multilocus Sequence Typing (Mlst)mentioning
confidence: 99%
See 2 more Smart Citations
“…ST 21 and ST 48 were the most prevalent ST in this study. These sequence types were frequently found in broiler meat or caeca swab samples by other authors (Di Giannatale et al, 2016;Wieczorek, Denis, Lachtara, & Osek, 2016;G. Zhang, Zhang, Hu, Jiao, & Huang, 2015), while ST 45 predominated in sample from Finnish broilers and human patients for years (Llarena, Huneau, Hakkinen, & Hänninen, 2015).…”
Section: ! Discussionmentioning
confidence: 68%